Identification of Phenylureidoglucosamines as a Novel T-type Calcium Channel Blocker - 한호규; 신동윤; 남기달; 배수열; 강호원; Jung-Sup Lim (한국키틴키토산학회, 2006)
We have found phenylureidoglucosamines as a novel scaffold for T-type Ca2+channel blocker and evaluated for the inhibitoryactivities against α1H, one of the isoforms of the T-type Ca2+channel subfamily. Among them, 3,4-dichlorophenylureidoglucosamineshowed the most potent blocking activity.